2018
DOI: 10.1080/02508060.2017.1393713
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of community-based adaptation strategies for droughts and floods in Kenya and the Central African Republic

Abstract: This paper discusses community-based adaptation strategies for droughts and floods in small watersheds in Kenya and the Central African Republic. Survey data on adaptation strategies and annual rainfall data in the watersheds were used to assess the occurrence of floods and droughts, and their impacts. In both areas, the main adaptation strategy for floods is temporary relocation. For droughts, changing livelihood activities was the main adaptation strategy, while relief-seeking applied to both droughts and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…This included articles on the impact of agricultural interventions and farmer perceptions in Afghanistan [ 34 , 37 ], and determining adaptation implementation and perception among farmers in Myanmar [ 55 , 68 ]. There were a few studies comparing farmer adaptation across countries, for example between Lebanon and Germany [ 19 ] and between Central African Republic and Kenya [ 51 ]. For both Mali and Nigeria, more than half of the articles for each country related to the food sector, ranging from smallholder farmers in Mali [ 57 ], to articles on specific drought-tolerant crops [ 77 ] and farmers of fruits and vegetables in Nigeria [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…This included articles on the impact of agricultural interventions and farmer perceptions in Afghanistan [ 34 , 37 ], and determining adaptation implementation and perception among farmers in Myanmar [ 55 , 68 ]. There were a few studies comparing farmer adaptation across countries, for example between Lebanon and Germany [ 19 ] and between Central African Republic and Kenya [ 51 ]. For both Mali and Nigeria, more than half of the articles for each country related to the food sector, ranging from smallholder farmers in Mali [ 57 ], to articles on specific drought-tolerant crops [ 77 ] and farmers of fruits and vegetables in Nigeria [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to the study of Devcota et al, (2014) in Nepal that showed that the community had used their local knowledge to forecast the flooding such as the movement of cloud and therefore, they had prepared a temporary location to rescue themselves. Also, in both areas within the communities of Kenya and Central Africa, their main adaptation strategy for floods is temporary relocation (Nguimalet, 2018). Further, the study of Danso and Addo (2016) at Sekondi-Takoradi Metropolis, in Ghana suggests that mutual coping strategies adopted by residents in all the communities were temporary relocation of homes, transfer of properties to neighbor's and building of floods steps.…”
Section: Community Adaptationmentioning
confidence: 99%
“…For Birkmann (2007), difficulties in recovering from the negative impacts of hazardous events also generate vulnerability, which makes coping and recovering part of its assessment. Therefore, we suggest that a combination of institutional and social strategies to provide better financial conditions and generate enhanced risk perception and coping capacity must be implemented in the city as resources to decrease flood vulnerability and increase resilience (Nguimalet 2018).…”
Section: Aspects Generating the Flood Vulnerabilitymentioning
confidence: 99%